Netflix Murah by Ama / Amalia Nadiah Ahmad Suffian - Ahmad Suffian, Amalia Nadiah (2021)
Netflix Murah by Ama provide a service where we are the cheapest and easiest platform for the customers that want to subscribe to Netflix. Our business offers affordable prices for our customers by giving a different low range of prices for each Netflix premium account based on the customers’ budgets. People of all ages would enjoy watching Netflix with their family especially during the lockdown in the pandemic nowadays which therefore included in the target market. Netflix Murah by Ama provide a few packages for both shared account and private account which is called Platinum Premium and Prime Premium accounts. The Netflix premium accounts provided by Netflix Murah by Ama are not only affordable in price, but it is also less hassle for the customers to subscribe as the customers did not need to use their debit or credit card. They only need to pay us and we will process their Netflix accounts immediately within minutes. Netflix Murah by Ama owned and worked by Amalia Nadiah binti Ahmad Suffian. Our business used Facebook Page as a platform for us to attract online customers and generate more sales from online platform. Teaser posts, soft sell and hard sell are included on Netflix Murah By Ama Facebook Page to promote our services to our customers and Facebook page followers. After we had registered on E-Commerce Application, Netflix Murah by Ama began to operate the business on 14 th April 2021. Netflix Murah by Ama not only focused on any specific are for the target market as our customers could be from anywhere because they will be searching a platform with affordable price to subscribe official Netflix. This is in line with our market strategy that is used by Netflix Murah by Ama where we have the list of Netflix accounts for an affordable price, we also do promotion during special occasion and celebration. Our strategy will attract more customers to make use of the services that we provided so that it will meet their needs and wants.